Chronical abdominal pain in children: management in the Communitary Medical Consultation - Sergio Luis González López; Armando Alvarez Corcuera; Zoe Quintero Delgado; Berta Fonseca Romero; Carlos Cabrera Machado; Lorenzo Pérez Romano (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2007)
The term recurrent abdominal pain is characterized by the presence of three or more episodes of abdominal pain in a three-months period although in clincal practice, this term is applied to intermittent episodes of pain in a period of more than one month. This definition is arbitrary causing debates and errors in diagnosing the patient. The term chronic abdominal pain is accepted nowadays which is the one that comprises the constant or intermittent abdominal pain of long duration, functional or organic. In this paper a bibliographical review on chronic abdominal pain in children is carried out. A critical analysis of the evaluation of the patient with this disorders is done as well as the management to follow with them in the primary attention and, the pharmachlogical and non pharmachlogical treatment of the patient with functional pain.